Motivasi Sebagai Variabel Mediasi Kompensasi terhadap Kinerja UMKM: Studi Kasus pada Sentra Industri Tempe dan Keripik Tempe Sanan - Sri Wahyuni; Abraham Ruylthon Illu (Jurnal Ekonomi Pertanian dan Agribisnis, 2023)
This study specifically tries to see the effect of compensation on the employee performance of MSMEs with motivation as a mediating variable at the Sanan Tempe Chips Industry Center. The method in this study is a type of quantitative research using Structural Equation Modeling (SEM) analysis with the WarpPLS approach. This study also uses the Sobel Test to analyze the significant value of the indirect relationship between compensation and employee performance mediated by motivation. In-depth interviews using questionnaires and direct observation were conducted to obtain primary research data. Meanwhile, secondary data was obtained through literature studies from various sources related to the research. A total of 60 respondents were selected as samples in this study using a simple random sampling technique. The results showed that the motivation variable had a significant effect as a mediating variable on the relationship between compensation and employee performance. This means that compensation has an indirect effect on employee performance through motivation.